2022
DOI: 10.1111/pace.14218
|View full text |Cite
|
Sign up to set email alerts
|

CRT implantation after transvenous lead/device extraction (TLE) in a patient with COVID‐19: Endocarditis triggered by syndrome coronavirus 2 (SARS‐COV‐2) infection? A case report

Abstract: In the era of coronavirus disease 2019 (COVID‐19), the management of cardiac implantable electronic devices infections with concomitant viral infection has not been completely defined yet. In this explorable context, we report the first experience of a Cardiac resynchronization therapy with defibrillator (CRT‐D) implantation after transvenous lead extraction for endocarditis in a COVID‐19 patient. We describe both the measures and procedures implemented to reduce the cross‐infection in the operating room and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Twenty-one cases from 20 publications that satisfied inclusion criteria were identified 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ( Figure 1 ). There were 8 cases in the United States, 7 in Europe (Italy 3, Spain 2, United Kingdom 1 and Greece 1), 3 in the Middle East (Iran, Morocco, Tunisia), 2 in South America (Brazil and Ecuador), and 1 in Asia (Indonesia).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one cases from 20 publications that satisfied inclusion criteria were identified 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ( Figure 1 ). There were 8 cases in the United States, 7 in Europe (Italy 3, Spain 2, United Kingdom 1 and Greece 1), 3 in the Middle East (Iran, Morocco, Tunisia), 2 in South America (Brazil and Ecuador), and 1 in Asia (Indonesia).…”
Section: Resultsmentioning
confidence: 99%
“…The second case reported by Romeo et al [ 4 ] had a history of prior cardiac surgery, and he was treated with corticosteroids, long broad-spectrum antibiotics, and immunosuppressors during his prolonged ICU stay with COVID-19 illness; he was later readmitted with a fungal infection. Vivo et al [ 5 ] reported a third case with preexisting cardiac disease and an implanted device in situ. He had COVID-19 pneumonia as well as Staphylococcus epidermidis -positive infective endocarditis at the same time.…”
Section: To the Editormentioning
confidence: 99%
“…Their fourth concern was that endocarditis was not mentioned as a cardiac complication of COVID-19, which had recently been reported in a few case reports [3][4][5]. However, patients with preexisting cardiac conditions, including prosthetic valves and implanted devices, were already excluded from our study [1].…”
Section: To the Editormentioning
confidence: 99%
“…Therefore, we should be informed how many of the included patients had a prosthetic valve or carried a device. Pacemakers, implantable cardioverter defibrillators, and cardiac resynchronisation therapy (CRT) system seem to carry also an increased risk of SARS-CoV-2-related endocarditis [ 6 ].…”
mentioning
confidence: 99%